2008
DOI: 10.1111/j.1740-0929.2008.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of approach direction and pace on flight distance of beef breeding cows

Abstract: The aim of this study is to determine the effect of approach direction and pace on flight distance of beef breeding cows. Five Japanese Black breeding cows were used as experimental cattle. Three approach directions were tested; that were the approach toward the head of the test cow from the front direction (FRONT), the approach toward to the foreleg of the test cow from the right or left (SIDE) and the approach toward to hind‐leg of the test cow diagonally from the right or left rear (BACK). Three levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Schematic examples of human-interaction tests (presence, approach, contact, and restraint) that can be conducted with range cattle are presented in Figure 2 . The schematic examples involving human presence and approach with an unfamiliar human are adapted from studies that assess human interactions in a ‘home’ or grazing environment [ 99 , 107 , 109 , 128 ], presence and approach with a speaker and restraint schematic examples are derived from experiences undergone by authors on unpublished pilot studies and studies with wildlife that utilize speakers.…”
Section: Recommendations For Future Hai Research In Rangeland Cattmentioning
confidence: 99%
“…Schematic examples of human-interaction tests (presence, approach, contact, and restraint) that can be conducted with range cattle are presented in Figure 2 . The schematic examples involving human presence and approach with an unfamiliar human are adapted from studies that assess human interactions in a ‘home’ or grazing environment [ 99 , 107 , 109 , 128 ], presence and approach with a speaker and restraint schematic examples are derived from experiences undergone by authors on unpublished pilot studies and studies with wildlife that utilize speakers.…”
Section: Recommendations For Future Hai Research In Rangeland Cattmentioning
confidence: 99%
“…The human approach test evaluates the humananimal relationship (fear of humans) which has an impact on handler's safety and welfare and productivity of animals (Kilgour et al 2006;Kosako et al 2008;Gibbons et al 2009;Leruste et al 2012). Gibbons et al (2009) reported that intra-animal consistency in flight response of dairy cows to an approaching human differed among human approach situations, being greatest when the animals were standing idle in the passageway of the home-pen followed by lying down and at the feedface.…”
Section: Introductionmentioning
confidence: 99%
“…The flight distance of each steer was measured over three consecutive days in August 2007 in the lowland pasture described above, using the method of Kosako et al . (). The experimenter walked around the herd for 30 min initially, to habituate the animals to their presence.…”
Section: Methodsmentioning
confidence: 97%